“Mindful of the hour of conquest”: Welsh Patriotism in Southey’s 1798 Morning Post Poems - Jones, Matthew (Romanticism on the Net)

(untitled) (Université de Montréal, 2017)
This essay examines the six poems on Welsh subjects that Southey published in the Morning Post in 1798, specifically in the context of their being written during a time of political oppression. As scholars have pointed out, during this period Southey masked his poetry’s radical messages in historical or abstract terms in order to evade allegations that he was being politically subversive. But, these accounts have overlooked how in these Welsh poems Southey weaves a radical vision of Welsh history that he ultimately brings into modernity, as well as how this link to the present depends upon contemporary Welsh culture (and various English views of it). This essay focuses on how Southey’s repetition and development of key terms across the poems, such as “patriotism,” “gallantness,” and “stranger,” operate in order to unite Welsh and English people against common transhistorical forces such as “Treachery” and “Power.” A focus on such themes elevates their permanence across time and space, and also allows Southey to bring the people of Britain together through shared histories of conquest and subjugation. Finally, by repeatedly emphasizing Wales’s current pacifism despite its charged histories Southey funnels radical potential into a living community without identifying it as a potential target for repressive state measures.